Protocol-Guided Suctioning for Safe Airway Management in Hemorrhagic Stroke Patients with External Ventricular Drainage: A Case Study - Tuti Nurlela; Lisbet Octovia Manalu; Tonika Tohri; Istianah Istianah (STIKep PPNI Jawa Barat, 2026)
Background: Ineffective airway clearance is a frequent nursing diagnosis in critically ill patients, particularly those with hemorrhagic stroke who experience decreased consciousness and impaired cough reflex. Accumulation of airway secretions increases the risk of hypoxia, aspiration, and respiratory complications, necessitating comprehensive airway management in the intensive care unit (ICU). Objective: This study aims to describe the implementation of suction-based nursing care in managing ineffective airway clearance in a patient with hemorrhagic stroke following external ventricular drainage (EVD). Methods: A single-patient case study was conducted in the ICU. Data were collected through comprehensive nursing assessment, direct observation, physical examination, and review of medical records. Nursing interventions were implemented based on clinical guidelines, including airway monitoring, positioning, oxygen therapy, and suction procedures. Data were analyzed descriptively to evaluate changes in clinical indicators over a five-day observation period. Results: Following structured airway management, progressive improvement in respiratory parameters was observed. Oxygen saturation (SpO₂) increased from 94% at baseline to 98% by Day 5, while respiratory rate decreased from 30 to 18 breaths per minute. Secretion volume reduced from approximately 25–30 ml/day to 8–10 ml/day, accompanied by changes in consistency from thick and viscous to thin and clear. Auscultation findings improved from bilateral rhonchi with gurgling to clear vesicular breath sounds. No adverse events or signs of neurological instability were observed during suction procedures. Conclusion: This case study demonstrates that structured, suction-based nursing care may effectively improve airway clearance and respiratory status in critically ill hemorrhagic stroke patients. Early and carefully monitored airway interventions can support oxygenation and reduce secretion burden without compromising patient safety in the ICU